Socioeconomic Disparities in the Utilization of Spinal Cord Stimulation Therapy in Patients with Chronic Pain. Issue 1 (25th August 2020) - Orhurhu, Vwaire; Gao, Catherine; Agudile, Emeka; Monegro, Wendy; Urits, Ivan; Orhurhu, Mariam Salisu; Olatoye, Dare; Viswanath, Omar; Hirji, Sameer; Jones, Mark; Ngo, Anh; Aiudi, Christopher; et al.
Abstract: Objectives: Spinal cord stimulation (SCS) therapies are used in the management of patients with complex regional pain syndrome I (CRPS I) and failed back surgery syndrome (FBSS). The purpose of this study was to investigate the racial and health insurance inequalities with SCS therapy in patients with chronic pain who had CRPS I and FBSS. Methods: Patients with chronic pain who had a discharge diagnosis of FBSS and CRPS I were identified using the National Inpatient Sample database. Our primary outcome was defined as the history of SCS utilization by race/ethnicity, income quartile, and insurance status. Multivariable logistic regression was used to determine the variables associated with utilization of SCS therapy. Results: Between 2011 and 2015, 40, 858 patients who were hospitalized with a primary diagnosis of FBSS and/or CRPS I were identified. Of these patients, 1, 082 (2.7%) had a history of SCS therapy. Multivariable regression analysis revealed that compared to White patients, Black and Hispanic patients had higher odds of having SCS therapy (Black patients: odds ratio [OR] = 1.41; 95% confidence interval [CI], 1.12 to 1.77; P  = 0.003; Hispanic patients: OR = 1.41; 95% CI, 1.10 to 1.81; P  = 0.007). Patients with private insurance had significantly higher odds of having SCS therapy compared with those with Medicare (OR = 1.24; 95% CI, 1.08 to 1.43; P  = 0.003). Compared to patients with Medicare, Medicaid patients had lower odds of having SCS therapy (OR = 0.50; 95% CI, 0.36 to 0.70; P  < 0.001). Conclusions: Our study suggests that socioeconomic disparities may exist in the utilization of SCS among hospitalized patients with CRPS I and FBSS the United States. However, confirming these data from other administrative databases, in the outpatient setting, may shed more insight.